The Okule Cult Education and Practice in Ghana - Ntewusu, Samuel; Awubomu, Richard; Ntewusu, Diana Amoni; Adasi, Grace (Journal of Interdisciplinary Studies in Education, 2020)
Using oral interviews, archival sources, observation, and published materials, we discuss the recruitment and training processes of the Okule Cult, an all-female cult. We analyze information obtained from the Nawuris of Northern Ghana to give insights into the relevance of Okule education practices to communities in Ghana. Knowledge about how members of the Okule cult educate new inductees and younger members advances our understanding of the continued importance of African Traditional Education. It would aid efforts to decolonize education on the African continent. The findings of our study can help educational authorities provide a balanced and holistic educational experience to learners.